2013
DOI: 10.1371/journal.pone.0078002
|View full text |Cite
|
Sign up to set email alerts
|

Cataract, Visual Impairment and Long-Term Mortality in a Rural Cohort in India: The Andhra Pradesh Eye Disease Study

Abstract: BackgroundA large-scale prevalence survey of blindness and visual impairment (The Andhra Pradesh Eye Diseases Study [APEDS1]) was conducted between 1996-2000 on 10,293 individuals of all ages in three rural and one urban clusters in Andhra Pradesh, Southern India. More than a decade later (June 2009-March 2010), APEDS1 participants in rural clusters were traced (termed APEDS2) to determine ocular risk factors for mortality in this longitudinal cohort.Methods and FindingsMortality hazard ratio (HR) analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 42 publications
5
56
1
Order By: Relevance
“…Details of the methodology for APEDS, which was conducted between 1996 and 2000, are described elsewhere 3. Data on mortality were obtained during an exercise undertaken between June 2009 and January 2010, the purpose of which was to identify as many participants as possible from the original APEDS, and recruit them for subsequent re-examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the methodology for APEDS, which was conducted between 1996 and 2000, are described elsewhere 3. Data on mortality were obtained during an exercise undertaken between June 2009 and January 2010, the purpose of which was to identify as many participants as possible from the original APEDS, and recruit them for subsequent re-examination.…”
Section: Methodsmentioning
confidence: 99%
“…The associations of mortality and VI, lens status and ARMD have already been published 3. The purpose of this study is to explore whether glaucoma (POAG and angle closure disease), IOP, PXF and CDR are associated with a different mortality risk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A large body of data from cross-sectional and longitudinal studies report an association between diabetes and cataract. The Beaver Dam Eye Study (BDES), Blue Mountains Eye Study (BMES), and Visual Impairment Project have documented an association between diabetes and incidence of posterior subcapsular cataract (PSC) and, to a lesser extent, incidence of cortical cataract (CC).…”
mentioning
confidence: 99%
“…11 In addition to improving visual function, some evidences suggest that cataract surgery is associated with better chances of survival, although this has yet to be conclusive. [3][4][5][6][7][8][12][13][14][15] The Beaver Dam Eye Study (BDES) 5 found no association between cataract surgery and mortality in participants who did and did not undergo surgery, while in the Bristol Eye Hospital Study, 15 people who had undergone cataract surgery had a significantly lower mortality than the national and regional standardized mortality ratios (SMR ¼ 0.88 vs. 0.87). Although many studies assessed the association of cataract surgery with mortality, they compared operated people with unoperated people with or without cataract, or people in the general population, which complicated the interpretation of the role cataract surgery played in its association with mortality.…”
mentioning
confidence: 99%